Plan de negocio de una consultora de neuromarketing en la ciudad de Quito - Rodríguez Paredes, Gabriel Patricio (2016)
This project involved the development of a business plan of a consulting neuromarketing in Quito, with the main objective of providing solutions to improve decision-making and strategic development of large and medium companies in the Ecuadorian market. This project was carried out by running a client analysis, where the supply of the market research industry and the potential demand could be determined neuromarketing consultant. The main results of market research showed that 90% of respondents would be interested in receiving offers of neuromarketing. Similarly 88.1% of the professionals surveyed companies have done a market research study in the last year and that more than half the made semiannually, these are positive indicators for the project. The differentiation strategy is based on offering a service of quality. The key in the desired demand from potential customers is the strategic sales management and public relations, the same that will be supported in training and consumer education. The calculation of initial investment of the project is $ 100,000, due to the incorporation of the investment company half was financed by a loan and half in equity. Furthermore, it was estimated that from the third year the company begins to have economic returns. The analysis of the valuation of the investment business plan reflects the net present value of the investment is $ 13,954.82 at a rate of 12.5%, and likewise the internal rate of return is 17.82 %, this shows that once crossed the period of planning and projection, the investor gets the invested capital and generate additional economic benefit aside such figures recommend entrepreneurs to the project.